2017
DOI: 10.1590/0074-02760160557
|View full text |Cite
|
Sign up to set email alerts
|

Effect of secondary infection on epithelialisation and total healing of cutaneous leishmaniasis lesions

Abstract: BACKGROUND Cutaneous leishmaniasis (CL) generally presents with a single or several localised cutaneous ulcers without involvement of mucous membranes. Ulcerated lesions are susceptible to secondary contamination that may slow the healing process.OBJECTIVE This study verified the influence of non-parasitic wound infection on wound closure (epithelialisation) and total healing.METHODS Twenty-five patients with a confirmed diagnosis of CL and ulcerated lesions underwent biopsy of ulcer borders. One direct microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“… Layegh et al (2015) described that the simultaneous treatment for microbial agents did not influence on the healing of cutaneous lesions. Antonio et al (2017) showed that the presence of secretion and burning sensation produced by bacterial infection influenced epithelization but not the total healing time. On the other hand, several authors have demonstrated the influence of secondary bacterial infections on lesion development and healing delay ( Vera et al, 2001 ; Ziaie and Sadeghian, 2008 ; Sadeghian et al, 2011 ; García-Bustos et al, 2016 ).…”
Section: The Host Point Of Viewmentioning
confidence: 99%
See 1 more Smart Citation
“… Layegh et al (2015) described that the simultaneous treatment for microbial agents did not influence on the healing of cutaneous lesions. Antonio et al (2017) showed that the presence of secretion and burning sensation produced by bacterial infection influenced epithelization but not the total healing time. On the other hand, several authors have demonstrated the influence of secondary bacterial infections on lesion development and healing delay ( Vera et al, 2001 ; Ziaie and Sadeghian, 2008 ; Sadeghian et al, 2011 ; García-Bustos et al, 2016 ).…”
Section: The Host Point Of Viewmentioning
confidence: 99%
“…Secondary bacterial infections in cutaneous lesions of leishmaniasis are very common and the most frequent bacterium observed is Staphylococcus aureus ( Ziaie and Sadeghian, 2008 ; AlSamarai and AlObaidi, 2009 ; Layegh et al, 2015 ; García-Bustos et al, 2016 ; Antonio et al, 2017 ). In addition, Salgado et al (2016) have shown diversity in bacteria isolates obtained from lesions and the contralateral healthy skin of the same patient.…”
Section: The Host Point Of Viewmentioning
confidence: 99%
“…Survival analysis shows that the size and location of the lesion influence the epithelialization time in CL, although the complete healing time was not influenced by these factors [ 35 ], as noted by other authors [ 36 ]. Individuals from other Brazilian states than Rio de Janeiro had longer healing times, which might be correlated with a delay in diagnosis and difficulties in accessing the health unit for follow-up, a higher rate of absences and less adherence to the proposed therapy.…”
Section: Discussionmentioning
confidence: 96%
“…Among a cohort of 25 CL patients, the presence of Staphylococcus aureus , Pseudomonas aeruginosa , Enterococcus faecalis , Streptococcus pyogenes and Candida parapsilosis was detected. [130]. The presence of bacteria in the ulcer border and ‘pain’ and ‘pruritus’ had no influence on wound closure, the presence of ‘secretion’ and ‘burning sensation’ delayed epithelialization time but not total healing time.…”
Section: Multiple Nano-drug Delivery Systems For Simultaneous Leishma...mentioning
confidence: 99%